Patients with Cardiovascular Implantable Electronic Devices in the Era of COVID-19 and Their Response to Telemedical Solutions - Diana Paskudzka; Łukasz Januszkiewicz; Roman Załuska; Agnieszka Kołodzińska; Łukasz Łyżwiński; Marcin Grabowski (Medicina, 2022)
Background and objectives: The COVID-19 pandemic has transformed the healthcare system, leading to the rapid implementation of telemedical solutions, especially in cardiology. The aim of this survey was to evaluate the patients (pts) with cardiac implantable electronic devices (CIED) perspectives on the telemedicine elements such as teleconsultation, telemonitoring, and e-prescription. Materials and methods: An anonymous questionnaire was created and delivered to CIED pts who came to the ambulatory outpatient clinic. In this survey, we evaluated teleconsultation, home monitoring systems, and e-prescription in the 17 single-choice and multiple-choice questions and a rating on a scale of 0 to 10. Results: During the four-month period, 226 pts (58% male) completed the questionnaire. Regular visits were most frequent in pts living in the urban area where the clinic was located, and least frequent in those living in rural areas (p = 0.0158). Moreover, 89 pts (39%) had teleconsultation before CIED interrogation, and satisfaction was 99%; 24 pts (11%) had home-monitoring control and 135 pts (60%) would have liked to have this opportunity; 88 pts (34.5%) would be able to pay additional costs for home-monitoring, with a mean amount of 65 PLN (±68.24). The e-prescription system was used by 203 pts (90%), and it was evaluated with 8.6 points (±2) on a scale from 0 to 10 points. Conclusions: The COVID-19 pandemic disrupted the previous functioning of the health system, and telemedicine became an alternative to traditional ambulatory visits and proved to be essential in the continuity of patient care. There is a substantial need for further development of telemedicine solutions in the healthcare system.